2008
DOI: 10.1109/tasl.2008.2004297
|View full text |Cite
|
Sign up to set email alerts
|

Using Kernel Discriminant Analysis to Improve the Characterization of the Alternative Hypothesis for Speaker Verification

Abstract: Abstract-Speaker verification can be viewed as a task of modeling and testing two hypotheses: the null hypothesis and the alternative hypothesis. Since the alternative hypothesis involves unknown impostors, it is usually hard to characterize a priori. In this paper, we propose improving the characterization of the alternative hypothesis by designing two decision functions based, respectively, on a weighted arithmetic combination and a weighted geometric combination of discriminative information derived from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…A support vector machine-based classifier was used for speaker verification utilizing the Gaussian mixture model (GMM) [4]. They achieved an equivalent error rate of 4.92% and 7.78% in the 2006 NIST speaker recognition evaluation test.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A support vector machine-based classifier was used for speaker verification utilizing the Gaussian mixture model (GMM) [4]. They achieved an equivalent error rate of 4.92% and 7.78% in the 2006 NIST speaker recognition evaluation test.…”
Section: Related Workmentioning
confidence: 99%
“…Research bodies and individuals have suggested numerous strategies to combat audio spoofing assaults [3]. Moreover, advanced MLbased approaches are employed to differentiate audio using knowledge-based and data-driven countermeasures [4].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, various machine learning and deep learning-based works have been proposed to detect forged speech. In [17], an SVM-based classifier has been utilized as AVS employing GMM. They attained an equal error rate of 4.92% and 7.78% on the 2006 NIST for speaker identification core test.…”
Section: Iiirelated Workmentioning
confidence: 99%